PENGARUH PENGGUNAAN ALAT PERAGA DALAM PEMBELAJARAN STRUKTUR LAPISAN BUMI TERHADAP HASIL BELAJAR SISWA - Zidny, Verga; Erman, Erman; Susiyawati, Enny (Universitas Negeri Surabaya, 2025)
This study aimed to describe the effect by implementing the structure of earth’s layers teaching aid in student cognitive learning outcomes of grade VII junior high school. The type of research used was pre-experimental design research through one group pretest-posttest design. The subjects in this study were 33 grade VII students of Public Junior High School in Sidoarjo City. Data collection techniques used was test methods include a pretest posttest of 25 multiple-choice questions based on paper and pencil tests. Learning outcomes data were analyzed using Kolmogorov-Smirnov’s normality test to see whether the data was normally distributed or not, then the N-Gain test to measure the increase in student learning outcomes and t-test in pairs in data of learning outcomes before and after treatment. The results showed that the influence by implementing the structure of earth’s layers teaching aid in student cognitive learning outcomes of grade VII junior high school students was seen to be increased. It shows on the Effect Size with 3.4 score which indicated as a high category and N-Gain test, an average score of 64% or 0.64 was obtained at a signification level of 5% or 0.05 which indicated as a medium category. Based on these results, it can be interpreted the implementation of the structure of earth’s layers teaching aid affects the improvement of students' cognitive learning outcomes.